2022
DOI: 10.1183/13993003.02467-2021
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene receptor antagonists and risk of neuropsychiatric events in children, adolescents and young adults: a self-controlled case series

Abstract: Leukotriene receptor antagonists (LTRAs) are widely used for asthma and allergic rhinitis (AR), but concerns about the risk of neuropsychiatric events (NPEs) have been raised since the first Drug Safety Communication by the US Food and Drug Administration in 2008. This study evaluates the association between LTRA and NPEs in children, adolescents, and young adults with asthma or AR.A self-controlled case series study was conducted using the Korean National Health Insurance Service claims database from two thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…This study reported a high prevalence of adverse drug reactions among 123 patients (31.9%), sleep disturbance was the most common (ADRs). Since 2008, there has been an increasing number of reports on potential adverse drug reactions to montelukast, including irritability, aggressiveness, and sleep disturbances, usually occurring after 1 week of commencing therapy and occurring in up to 10% of children [ 3 , 4 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The World Health Organization (WHO) pharmacovigilance database reported multiple adverse effects, including depression, headache, aggression, suicidal ideation, anxiety, insomnia, abnormal behavior, nightmares, shortness of breath, abdominal pain, nausea, rash, dizziness, myalgia and muscle spasm [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reported a high prevalence of adverse drug reactions among 123 patients (31.9%), sleep disturbance was the most common (ADRs). Since 2008, there has been an increasing number of reports on potential adverse drug reactions to montelukast, including irritability, aggressiveness, and sleep disturbances, usually occurring after 1 week of commencing therapy and occurring in up to 10% of children [ 3 , 4 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The World Health Organization (WHO) pharmacovigilance database reported multiple adverse effects, including depression, headache, aggression, suicidal ideation, anxiety, insomnia, abnormal behavior, nightmares, shortness of breath, abdominal pain, nausea, rash, dizziness, myalgia and muscle spasm [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the postmarketing surveillance has observed that montelukast may induce adverse neuropsychiatric events (NPEs) and nightmares [33 ▪ ,34]. The risks of NPEs following LTRAs use vary over time (increasing in 4–7 days and 8–14 days after initiation of LTRA) and ages (increasing in adolescents and young adults but decreasing in children) [33 ▪ ]. In most cases, the nightmares disappear upon drug withdrawal, but in some cases, it takes a long time until the nightmares diminish [34].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Clinical trials (35 RCTs in adults and 11 in children) have revealed that the incidence of montelukast-induced adverse events is 2.73%, which is comparable with that of placebo [32]. However, the postmarketing surveillance has observed that montelukast may induce adverse neuropsychiatric events (NPEs) and nightmares [33 ▪ ,34]. The risks of NPEs following LTRAs use vary over time (increasing in 4–7 days and 8–14 days after initiation of LTRA) and ages (increasing in adolescents and young adults but decreasing in children) [33 ▪ ].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…2 However, evidence regarding the risk of NEs associated with LTRAs has been conflicting. [3][4][5] To the best of our knowledge, no previous studies have reported the association of exposure to LTRAs during pregnancy with the risk of NEs in offspring. The present cohort study aimed to address this research question.…”
Section: Introductionmentioning
confidence: 98%
“…Over the years, the US Food and Drug Administration has monitored postmarketing data about the potential harm of neuropsychiatric events (NEs) associated with montelukast, the first type of LTRAs, and issued boxed warnings about serious NEs associated with montelukast use in 2020 . However, evidence regarding the risk of NEs associated with LTRAs has been conflicting . To the best of our knowledge, no previous studies have reported the association of exposure to LTRAs during pregnancy with the risk of NEs in offspring.…”
Section: Introductionmentioning
confidence: 99%